2019
DOI: 10.3102/0002831218816955
|View full text |Cite
|
Sign up to set email alerts
|

Racial Identity, Racial Discrimination, and Classroom Engagement Outcomes Among Black Girls and Boys in Predominantly Black and Predominantly White School Districts

Abstract: This study examined the associations among racial identity beliefs (centrality and public regard), racial discrimination, and academic engagement outcomes among 1,659 African American adolescents across two demographically distinct school districts, one predominantly Black, working class ( n = 1,100) and one predominantly White, middle class ( n = 559). Across these districts, the youths reported that race was a central aspect of their identity and demonstrated varying levels of public regard. Racial discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 80 publications
4
81
0
Order By: Relevance
“…Harris (2010) suggested that school peer effects may also be driven by ''group-based contagion'' mechanisms, in the sense that peers influence one another's beliefs and values. Moreover, the fact that public school teachers are predominantly White, often with little experience working with students of color, may lead to cultural disconnects that influence classroom processes and climates (Leath, Mathews, Harrison, & Chavous, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Harris (2010) suggested that school peer effects may also be driven by ''group-based contagion'' mechanisms, in the sense that peers influence one another's beliefs and values. Moreover, the fact that public school teachers are predominantly White, often with little experience working with students of color, may lead to cultural disconnects that influence classroom processes and climates (Leath, Mathews, Harrison, & Chavous, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…During the period of adolescence, race may become more salient for Black youth (Tatum, 1997) as they develop the cognitive capacity to be able to notice both nonverbal and verbal cues about race within their school environment (Rosenbloom & Way, 2004). Experiencing interpersonal discrimination and seeing unfair treatment toward those who share similar social identities may lead to negative perceptions of school racial climate, negative internalized beliefs and attitudes toward one’s race, and risks for low school engagement (Butler-Barnes et al, 2013; Leath et al, 2019). In contrast, Black adolescents may possess particular assets that buffer the deleterious impact of such negative experiences on school engagement and promote a positive private regard (DeCuir-Gunby et al, 2012; Dotterer et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, though there are no discernible differences in the way that Black students behave in school, according to a 2018 bipartisan report from the U.S. Government Accountability Office (2018), Black students accounted for 15.5% of all public school students but represented about 39% of students suspended from school-an overrepresentation of about 23%. Policies that govern selection criteria for special academic programs (gifted or special education) and discipline guidelines used for suspension may impede racial equity and contribute to declines in school engagement for Black adolescents (Leath et al, 2019). Perceptions of unfair treatment and inequity directed toward others who share similar social identities are considered to lead to negative views toward school and affirm negative beliefs toward one's racial group (Butler-Barnes et al, 2013).…”
Section: School Climatementioning
confidence: 99%
See 1 more Smart Citation
“…In identifying, naming, and publicly stating their position around DIRE, participants of such institutions—especially those from minoritized backgrounds who perhaps experience the most consequences from lack of or unclear statement—can present their best selves. 44 When DIRE policy statements are divorced from or weakly aligned with the organization’s advertised mission, vision, strategic plan, and employee evaluation metrics, an ugly underbelly emerges—between what is publicly stated and what exists behind closed doors—where discrimination, lost voices, nepotism, sexism, racism, and other “isms” live. Poorly constructed statements then set the stage for environments which further exclude minoritized groups.…”
Section: Dire Policy Statements As a Catalytic Mechanismmentioning
confidence: 99%